2009
DOI: 10.1177/0956797609356511
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Individual Differences in the Cognitive Abilities of Children and Chimpanzees

Abstract: Most studies of animal cognition focus on group performance and neglect individual differences and the correlational structure of cognitive abilities. Moreover, no previous studies have compared the correlational structure of cognitive abilities in nonhuman animals and humans. We compared the structure of individual differences of 106 chimpanzees and 105 two-year-old human children using 15 cognitive tasks that posed problems about the physical or social world. We found a similar factor of spatial cognition fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
150
4
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(167 citation statements)
references
References 35 publications
7
150
4
6
Order By: Relevance
“…They have also found that this general cognitive performance is correlated quite strongly with brain size, corrected slightly for the effects of body size [25,26]. Similar intraspecific studies on cotton-top tamarins (Saguinus oedipus) support the notion of general intelligence [81], whereas results on chimpanzees also agree if we accept the finding [82] that spatial cognition is on a separate dimension. Domain-general cognitive abilities may be even more widespread in the animal kingdom and also occur in other mammals and birds [83][84][85].…”
Section: Box 2 General Intelligence In Nonhumanssupporting
confidence: 65%
“…They have also found that this general cognitive performance is correlated quite strongly with brain size, corrected slightly for the effects of body size [25,26]. Similar intraspecific studies on cotton-top tamarins (Saguinus oedipus) support the notion of general intelligence [81], whereas results on chimpanzees also agree if we accept the finding [82] that spatial cognition is on a separate dimension. Domain-general cognitive abilities may be even more widespread in the animal kingdom and also occur in other mammals and birds [83][84][85].…”
Section: Box 2 General Intelligence In Nonhumanssupporting
confidence: 65%
“…In humans, the similar personality construct, agreeableness, is correlated with cognitive processing of other's emotions (Nettle and Liddle 2008). It is tempting to speculate that individual differences in cognitive performance (Herrmann et al 2010) may underpin the differences in positive affect also in chimpanzees.…”
Section: Discussionmentioning
confidence: 99%
“…At another extreme, more flexible cognition may be required to come up with innovations that deviate from more pre-potent action patterns and additionally require long periods of individual practice and social input to use the tool more systematically and habitually. Dolphins, for instance, are not 'built' for manipulative tool use, but can readily integrate acoustic and visual inputs to represent objects [117,118], and use their cognitive ability to solve problems with tools in laboratory and field, at least when the conditions call for it. Calves of bottlenose dolphins spend thousands of hours observing maternal tool use before the first instances of tool use are observed [48].…”
Section: Discussionmentioning
confidence: 99%